The Contextual Approach in Neuroscience Teaching: Enhancing Understanding and Arabic Language Skills - Nurbaiti, Nurbaiti; Husna, Juliatun (Yayasan Nanggroe Aceh Mulia, 2025)
The contextual approach in teaching Sharaf enhances understanding and Arabic language skills by connecting Nahwu theory with practical application. This approach utilizes text analysis, case studies, group discussions, and experiments to study Sharaf concepts such as i’rab, qaawafi, asma’, and af’al. Research results indicate a significant improvement in students' understanding and analytical skills. The contextual approach is a learning method that links subject matter with real-life experiences or everyday situations of students. Its goal is to help students understand concepts more easily and apply them practically. In the context of teaching Sharaf, this approach involves the use of relevant examples, interactive media, and the integration of materials with Qur'anic texts or daily conversations.